Investment Financing in the Wake of the Crisis : The Role of Multilateral Development Banks - Chelsky, Jeff (World Bank, Washington, DC, 2015)
Sustained growth in emerging markets and developing economies requires long-term, reliable capital to finance productive investment, including in basic infrastructure. However, the availability and composition of long-term financing is constrained, partly due to fragile market conditions and cyclical weaknesses in parts of the global economy, as well as longer-term trends. This has had a particularly negative impact on developing economies that do not have reliable access to international bond markets and on sectors that have traditionally relied on bank lending (such as infrastructure). At the same time, fiscal space has been eroded by the crisis, and the direct lending capacity of Multilateral Development Banks (MDBs) remains constrained. This heightens the importance of the catalytic role of the official sector in mobilizing long-term financing from the private sector by drawing on its ability to reduce and share risk. This note explores some of the ways in which MDBs are equipped to serve this purpose.